Starting a business from home : your guide to planning your home start-up, reaching a market and creating a profit / Colin Barrow - Barrow, Colin (Business success, 2017)
"For aspiring entrepreneurs and business owners, the possibilities are limitless. The flexibility, freedom and cost-effectiveness that starting-up in the home offers means that more and more entrepreneurs are choosing this as the best location to agilely launch their business. Starting a Business from Home gives you the valuable advice you need on how to run a successful business from your own desk and, crucially, how to rise to the challenge of business expansion. Packed with practical advice, Starting a Business from Home covers how to research your market, business ownership and titles issues, raising money and managing your finances, building and operating a website, writing a business plan, preparing your accounts, taking your product to market and expanding overseas--all from your home. Exercises, end of chapter actions and technical resources in the appendices mean that this is the ultimate practical guide for home-based entrepreneurs. Case studies from around the world showcase best practice and provide inspirational stories from successful businesses that began in the home."--Amazon.com.